Stents for transcatheter aortic valve replacement - Park, Kenneth Stuart (Division of Biomedical Engineering, 2018)
Rheumatic heart disease (RHD) is the leading cause of aortic valve disease in the world. Surgery to repair or replace the diseased valves is the only means to save a patient's life once the disease becomes symptomatic. Transcatheter aortic valve replacement (TAVR) has revolutionised the treatment of age-related degenerative aortic valve disease, but is currently not suitable for the majority of RHD sufferers due to the rapid degeneration of flexible leaflet valves in younger patients, contraindications of commercial devices to regurgitant or non-calcific aortic valve disease, and also due to resource or funding limitations. The current research project aimed to develop and test novel compressible balloon-expandable stents suitable for patients with symptomatic rheumatic aortic valve disease, and which would allow for a percutaneous polymeric valve to be manufactured, be crimped onto balloon-based devices, and be expanded into a compliant or non-calcific native aortic valve. Several stent concepts were developed and evaluated using Finite Element Analysis (FEA) and two favoured concepts were selected for more complex FEA, in which the balloon was simulated using an Ogden material model, and rigorous testing. The stent material, a nickel-cobalt-chromium alloy, was modelled as an isotropic elasto-plastic material with isotropic hardening. The novel stent designs incorporated a native leaflet-mimicking crown shape for continuous leaflet attachment and mechanisms to anchor the stented valve within compliant aortic roots. The first of the favoured designs provided tactile location during delivery and anchored using self-expanding arms on a balloon-expandable frame of the same material ("self-locating stents"). The second design anchored using arms that protruded during deployment as a consequence of plastic deformation incurred during crimping ("expanding arm stents"). Prototypes were successfully manufactured through laser cutting and electropolishing and showed good surface quality. In vitro testing included determination of crimping and expansion behaviour and measurement of mechanical properties such as resistance to migration in the anatomy. Valve performance was evaluated through in vitro haemodynamics in a pulse duplicator and durability was tested in a high-cycle fatigue tester. Simulated use testing was performed using cadaveric animal hearts. Finally, valves were also implanted into the aortic valve position of pigs (in acute termination experiments) through a transapical approach in order to verify valve deployment behaviour and function in vivo, and determine the stent's ability to anchor in the native anatomy. Stents could be crimped to diameters below 6mm and deployed using commercial balloons and proprietary non-occlusive deployment devices. FEA simulations of stent crimping and deployment matched experimental behaviour well and provide a tool to optimise stent performance. Peak Von Mises stresses during deployment (1437 MPa and 1633 MPa for self-locating and expanding arm stents, respectively) were comparable to a "zig-zag" stent simulated for control purposes (1650 MPa). Radial strength, evaluated for expanding arm stents, was lower than the Control stent (116 N vs. 347 N). This design, although predicted to be safe under fatigue loading, had a lower fatigue safety factor than the Control stent. Stents resisted migration to forces of at least 22 N, which is four times greater than physiological loading on the valves. Polymeric valves incorporating the stents were constructed and demonstrated good in vitro haemodynamic performance (Effective Orifice Areas ≥2.0cm², ΔP<9 mmHg, regurgitation <6%) and durability of over 400 million cycles. Designs functioned as intended in simulated use tests. Valves constructed using self-locating stents could be successfully deployed without rapid pacing in eight of nine pigs, and valve position was correct in seven of these. Valves of expanding arm stents remained anchored in six of eight attempted implants in pigs. This study has demonstrated proof of concept for a novel balloon-expandable stent for a polymeric transcatheter heart valve that is capable of anchoring in a compliant native aortic valve.